(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article analyzes, from an ethnographical perspective, how the juridical went trough the transmission of memo- ries on the concentration camps experiences. More preci- sely, it approaches how the judiciary dimension frames the relationship between testimony (as memory and story) and witness (as individual, author and identity) in the earlier tes- timonies of the survivors of the concentration camp known as La Perla (Córdoba-Argentina).